Risky business: males choose more receptive adults over safer subadults in a cannibalistic spider. (25th April 2022) - Sentenská, Lenka; Scott, Catherine; Mouginot, Pierick; Andrade, Maydianne C B
Abstract: Understanding factors affecting male mate choice can be important for tracking the dynamics of sexual selection in nature. Male brown widow spiders ( Latrodectus geometricus ) mate with adult as well as immature (subadult) females. Mating with adults involves costly courtship with a repertoire of signaling behaviors, and typically ends with cannibalism ("self-sacrifice" initiated by male somersault). Mating with subadults involves brief courtship with behavioral repertoire reduced to one component (vibration) and no cannibalism. We examined male mate choice as a function of risks associated with different types of mates and the cues available to courting males. Previous studies showed male preference for adults based on air-borne pheromones, but it was unclear whether that preference is maintained after males reach female's webs. We show that males prefer adults also based on silk-borne contact cues. To determine which types of cues trigger different courtship components, we swapped adults and subadults between webs. We showed that contact with adult females' webs triggers two courtship behaviors from the repertoire, with adult female's bodies triggering additional behaviors. However, vibrational signals occur regardless of the web origin or female developmental stage. We conclude that males recognize subadult females as potential mates, but are more likely to invest in costly courtship behaviors and mating attempts with adults. In our experiments, subadults were less likely to mate than adults. We conclude that mating with adults could be the preferred option for males because of the higher likelihood of copulation, even at the cost of a higher risk of cannibalism. Abstract : In the brown widow spider, males can mate with non-cannibalistic immature (subadult) females, but they prefer mating with cannibalistic adults, using a more extensive repertoire of courtship behaviours and signals. We show that costly male courtship behaviours are triggered by cues on the female's web or body. Males engage in web-based courtship behaviours only upon contact with adult webs and costly female-oriented behaviour only upon contact with an adult female. We conclude that the reduced courtship and lack of cannibalism with subadults arises from male choice to reduce investment into subadult mating.